J/Ψ in nuclear matter - Krein, G. [UNESP] (IOP Publishing, 2013)
We report on recent estimates of the J/Ψ mass shift in infinite nuclear matter and finite nuclei arising from in-medium D and D* meson loops. The density dependence of the J/Ψ mass shift is evaluated employing medium-modified D and D* meson masses derived within the quark-meson coupling model. Using a local density approximation, J/Ψ-nuclear bound state energies are calculated for a range of nuclei. We predict that J/Ψ-nuclear bound states should be observed with a clear signal in experiments, provided the J/Ψ meson is produced in recoilless kinematics. © Published under licence by IOP Publishing Ltd.
Keywords: Bound state; Bound-state energies; Density dependence; Mass shift; Nuclear matters; Quark-meson coupling models; Colliding beam accelerators; Hadrons; Bosons